Equality and responsibility in education policy - Tamir, Y (Foundation for Law, Justice and Society, 2009)
The new social contract aims to establish a society in which individuals can live meaningful lives. While the state enjoys the outcome of citizens’ responsible acts it has a duty to create the necessary conditions for such actions, and in so doing to close social and economic gaps between families and individuals alike.